Contemporary Tailored Oncology Treatment of Biliary Tract Cancers - Fiona Turkes; Juliet Carmichael; David Cunningham; Naureen Starling (Gastroenterology Research and Practice)
Biliary tract cancers (BTCs) are poor prognosis malignancies with limited treatment options. Capecitabine has recently emerged as an effective agent in the adjuvant setting; however, treatment of advanced disease is still limited to first-line cisplatin and gemcitabine chemotherapy. Recent global efforts in genomic profiling and molecular subtyping of BTCs have uncovered a wealth of genomic aberrations which may carry prognostic significance and/or predict response to treatment, and several targeted agents have shown promising results in clinical trials. As such, the uptake of comprehensive genomic profiling for patients with BTCs and the expansion of basket trials to include these patients are growing. This review describes the currently approved systemic therapies for BTCs and provides insight into the emerging targeted and immunotherapeutic agents, as well as conventional chemotherapeutic regimes, currently being investigated in clinical trials.